2020
DOI: 10.12973/ijem.6.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Thai Students’ Perceived Teacher Support on Their Reading Ability: Mediating Effects of Self-Efficacy and Sense of School Belonging

Abstract: <p style="text-align: justify;">This study aimed to investigate whether Thai high school students’ perceived teacher support could enhance their reading ability through self-efficacy and sense of school belonging. The theoretical foundation of this study included the theory of social-motivational processes and social cognitive theory. Structural equation modeling was used for analysis and validation. The student questionnaire from the Programme for International Student Assessment (PISA) 2018 survey ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…Because of the pivotal role of teacher respect and teacher support in the language learning process ( Celkan et al, 2015 ; Wang and Guan, 2020 ; Sadoughi and Hejazi, 2021 ), a sizable number of inquiries have been dedicated to these variables and their scholastic outcomes [e.g., Miller et al (2017) , Singer and Audley (2017) , Feng et al (2019) , and Chang and Bangsri (2020) , among others]. Yet, the impact of these variables on learner grit has been overlooked by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the pivotal role of teacher respect and teacher support in the language learning process ( Celkan et al, 2015 ; Wang and Guan, 2020 ; Sadoughi and Hejazi, 2021 ), a sizable number of inquiries have been dedicated to these variables and their scholastic outcomes [e.g., Miller et al (2017) , Singer and Audley (2017) , Feng et al (2019) , and Chang and Bangsri (2020) , among others]. Yet, the impact of these variables on learner grit has been overlooked by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the findings of this study, it has been reported that self-efficacy is a significant part of science success. In the literature, there are many studies showing that there is a significant relationship between self-efficacy and academic success (Aktürk& Aylaz, 2013;Chang& Bangsri, 2020;Çalışkan, 2008;Doğan& Barış, 2010;Doğan, Beyaztaş& Koçak, 2012;Juan, Hannan &Namome, 2018;Maier& Curtin 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This assessment is conducted every 3 years and is divided into three main points, namely literacy, mathematics and science. The results in 2018 measured the abilities of 600,000 15-year-olds from 79 countries (Chang & Bangsri, 2020). Previously, the Organisation for Economic Cooperation and Development (OECD) announced the results of the 2018 PISA.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%